Proliferation induced by Plasmodium falciparum antigen and interleukin-2 production by lymphocytes isolated from malaria-immune individuals. - Theander, T G (1986)
Affinity-purified Plasmodium falciparum soluble antigens (SPAg) isolated from in vitro cultures of the parasite were shown to be relatively free of nonspecific polyclonal activators. To determine the presence of lymphocytes with specificity against SPAg in the peripheral blood of malaria-immune individuals, the proliferative response and the interleukin-2 (IL-2) production of SPAg-activated mononuclear cells (MNCs) from individuals unexposed, sensitized, and immune to malaria were measured. It was found that MNC isolated from malaria-immune individuals proliferated in response to SPAg and that this activation resulted in measurable IL-2 production in 5 of 10 MNC cultures. MNC isolates from most unexposed individuals did not respond to SPAg. To establish which cells responded to SPAg, different subpopulations of MNCs were tested. Only T helper cells were found to respond, and they responded only when cocultured with monocytes. The finding of parasite-specific T helper cells in the blood of malaria-immune individuals and the fact that some of these cells were able to produce IL-2 in vitro support the hypothesis that in malaria the cellular part of the protective immune response is initiated by immune T cells. These cells may activate nonspecific effector cells (i.e., macrophages) that eliminate the parasite.